Comparison of different activated agents on biomass-derived graphene towards the hybrid nanocomposites with zeolitic imidazolate framework-8 for room temperature hydrogen storage. Issue 2 (April 2021) - Arifin, N.F.T.; Yusof, N.; Nordin, N.A.H.M.; Bilad, M. Roil; Jaafar, J.; Ismail, A.F.; Aziz, F.; Salleh, W.N.W.
Abstract: Surface area and porosity are the main factors that affect hydrogen adsorption at room temperature. In this work, the preparation of rice husk derived graphene (GRHC) using two different activating agents, potassium hydroxide (KOH) and phosphoric acid (H3 PO4 ) without inert condition was demonstrated. GRHC KOH-activation (GRHC-KOH) exhibited larger surface area at 517.92 m 2 /g with higher total pore volume of 0.3346 cm 3 /g as compared to GRHC H3 PO4 -activation (GRHC-H3 PO4 ) at 315.07 m 2 /g surface area and 0.1795 cm 3 /g total pore volume. To demonstrate the effect of surface area and porosity towards hydrogen storage at ambient condition (25 ± 2 °C), GRHC-KOH and GRHC-H3 PO4 were added separately via in-situ in zeolitic imidazolate frameworks-8 (ZIF-8) to form a hybrid nanocomposites of ZGK and ZGH respectively. The formation of hybrid nanocomposites depicted that the surface area and pore volume increased almost three times higher in ZGK (1632.10 m 2 /g and 1.1694 cm 3 /g) and ZGH (748.12 m 2 /g and 0.6489 cm 3 /g) as compared to pristine GRHC. At 12 bar, ZGK exhibited the highest hydrogen storage, 1.48 ± 0.01 wt% while 1.00 ± 0.01 wt% was obtained in ZGH. The adsorption in both ZGK and ZGH were governed by chemisorption. The improvement of hydrogen storage at ambient temperature in ZGK might be due to the synergistic effect of both GRHC-KOH and ZIF-8 which enhanced the surface area and porosity of the hybrid nanocomposites. Graphical Abstract: ga1 Highlights: Activation of rice husk char (RHC) with potassium hydroxide (KOH) shows better physicochemical properties. Introduction of GRHC in ZIF-8 enhances the physicochemical properties of the nanocomposites. ZIF-8/GRHC-KOH activated (ZGK) shows the highest H2 storage (1.48 wt%) at 12 bar and room temperature condition